PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID PADA MATERI TRIGONOMETRI - Fithrotin Niswah; Roisatun Nisa' (Prodi Pendidikan Matematika FKIP Universitas Madura, 2022)
The purpose of this research is to produce an android application that is valid, practical, and effective which is used as a medium for learning mathematics. This type of research is research development using ADDIE (analysis, design, development, implementation, and evaluation) research method. At the analysis stage, the thing to do is analyze the characteristics of students and analyze the curriculum through interviews. From the results of interviews, it is known that the characteristics of students are influenced by their abilities, there are 2 groups of students' abilities, namely high and low ability students, and the applicable curriculum is the 2013 curriculum. At the design stage, product design is done, namely the collection of materials, images, questions, and flowchart creation. Validation results from media experts and material experts get an average value of 4.0 and 4.1 validators respectively so that the media is said to be valid. In the implementation stage, limited trials were conducted with using the test of learning results and student response questionnaires. At the time of pre-test obtained an average of 66.7 with unfinished criteria, while the average result of post-test is 85.6 with good criteria. Based on the assessment of the questionnaire responses, students obtained an average of 4,326 with very good criteria. This study shows that the learning media is valid, practical, effective.